Pengaruh Good Corporate Governance dan Corporate Social Responsibility terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Tika Oktarina; Maya Novianti; Lizvan M Sitorus; Sucipto Febrianto (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine the effect of Good Corporate Governance and Corporate Social Responsibility on Company Value with Financial Performance as an intervening variable. This study used 17 mining companies listed on the Indonesia Stock Exchange, selected using the purposive sampling method from the period 2019 to 2023. The statistical method used to test the hypothesis is SEM-PLS (Structural Equation Model - Partial Least Square). The results of this study prove that: 1) Good Corporate Governance has a significant negative effect on Financial Performance and Company Value, 2) Corporate Social Responsibility has a significant positive effect on Financial Performance and Company Value, 3) Financial Performance has a significant positive effect on Company Value, and is able to mediate the effect of Good Corporate Governance and Corporate Social Responsibility on Company Value. The implications are, 1) Good Corporate Governance must be maintained properly so that supervision and control of company activities are maximized so that Financial Performance can be maximized and then have an impact on a positive market response, 2) Corporate Social Responsibility is still carried out to attract investor trust so that they continue to provide a good response so that the company's value increases.